2014
DOI: 10.1089/scd.2014.0068
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Finger DHHC-Type Containing 13 Regulates Fate Specification of Ectoderm and Mesoderm Cell Lineages by Modulating Smad6 Activity

Abstract: Neither the roles of Asp-His-His-Cys (DHHC)-containing proteins in embryonic cell fate specification are well defined, nor the underlying mechanisms of their activity are well understood. Here, we compared the embryonic function of zinc finger DHHC-type containing (Zdhhc13) in zebrafish embryos and in an in vitro cell model. Zdhhc13, a critical regulator of bone morphogenetic protein (BMP) signaling, specifically bound to Smad6 to induce its perinuclear accumulation and degradation through a mechanism independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
(49 reference statements)
2
9
0
Order By: Relevance
“…This suggests that the nuclear localization of ERK1/2 is critical for its activation of Sox2 transcription. Monolayer P19 cells are capable of differentiating into endoderm-and mesoderm-like cells [26,27]. As we observed, melatonin treatment of P19 cells significantly increased the number of Sox2-positive cells during neural fate specification.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…This suggests that the nuclear localization of ERK1/2 is critical for its activation of Sox2 transcription. Monolayer P19 cells are capable of differentiating into endoderm-and mesoderm-like cells [26,27]. As we observed, melatonin treatment of P19 cells significantly increased the number of Sox2-positive cells during neural fate specification.…”
Section: Resultssupporting
confidence: 76%
“…Monolayer P19 cells are capable of differentiating into endoderm‐ and mesoderm‐like cells . As we observed, melatonin treatment of P19 cells significantly increased the number of Sox2‐positive cells during neural fate specification.…”
Section: Resultssupporting
confidence: 72%
“…Clinical phenotypes of mice lacking ZDHHC13 expression have been characterized in mice generated either by ethylnitrosourea mutagenesis (Saleem et al, 2010) or by direct and conditional knockout technologies (Chen et al, 2017a). A previous study on the role of ZDHHC13 in zebrafish embryonic development indicated that this protein could regulate ectoderm and mesoderm homeostasis via a PAT-independent mechanism (Chen et al, 2014). That finding prompted us to revisit the question of whether PAT enzymatic activity is indeed responsible for maintaining skin barrier integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Western blot and Whole‐mount immunostaining were described previously (Chen et al, ; Shi et al, ). The primary antibodies were as follows: for Western blotting: anti‐ERK1/2 (1:1000; Cell Signaling Technology), anti‐p‐ERK1/2 (1:1000; Cell Signaling Technology) and anti‐β‐actin (1:2000, Sigma); for whole‐mount immunostaining: acetylated α‐tubulin (1:200; Sigma).…”
Section: Methodsmentioning
confidence: 99%